Comparison of International Pediatric Sepsis Consensus Conference Versus Sepsis-3 Definitions for Children Presenting With Septic Shock to a Tertiary Care Center in India: A Retrospective Study*. Issue 3 (March 2019) - Sankar, Jhuma; Dhochak, Nitin; Kumar, Kiran; Singh, Man; Sankar, M. Jeeva; Lodha, Rakesh
Abstract : Objectives: To evaluate the proportion of children fulfilling "Sepsis-3" definition and International Pediatric Sepsis Consensus Conference definition among children diagnosed to have septic shock and compare the mortality risk between the two groups. Design: Retrospective chart review. Setting: PICU of a tertiary care teaching hospital from 2014 to 2017. Patients: Children (⩽ 17 yr old) with a diagnosis of septic shock at admission or during PICU stay. Interventions: None. Measurements and Main Results: We applied both International Pediatric Sepsis Consensus Conference and the new "Sepsis-3" definition (sepsis with hypotension requiring vasopressors and a lactate value of ≥ 2 mmol/L) to identify cases of septic shock by these definitions. Key outcomes such as mortality, proportion attaining shock reversal at 24 hours and organ dysfunction were compared between those fulfilling "Sepsis-3" definitions ("Sepsis-3" group) and those fulfilling "International Pediatric Sepsis Consensus Conference" definition ("International Pediatric Sepsis Consensus Conference" group). A total of 216 patients fulfilled International Pediatric Sepsis Consensus Conference definitions of septic shock. Of these, only 104 (48%; 95% CI, 42–55) fulfilled "Sepsis-3" definition. Children fulfilling "Sepsis-3 plus International Pediatric Sepsis Consensus Conference definitions" ("Sepsis-3 and International Pediatric Sepsis Consensus Conference" group) had lower proportion with shock resolution (61% vs 82%; relative risk, 0.73; 95% CI, 0.62–0.88) and higher risk of multiple organ dysfunction (85% vs 68%; 1.24; 1.07–1.45) at 24 hours. The mortality was 48.5% in "Sepsis-3 and International Pediatric Sepsis Consensus Conference" group as compared with 37.5% in the "International Pediatric Sepsis Consensus Conference only" group (relative risk, 1.3; 95% CI, 0.94–1.75). Conclusions: Less than half of children with septic shock identified by International Pediatric Sepsis Consensus Conference definitions were observed to fulfill the criteria for shock as per "Sepsis-3" definitions. Lack of difference in the risk of mortality between children who fulfilled "Sepsis-3" definition and those who did not fulfill the definition raises questions on the appropriateness of using this definition for diagnosis of septic shock in children. Abstract : Supplemental Digital Content is available in the text.